Bridging the Gap between Testing and Technology in Schools - Russell, Michael; Haney, Walt (Education Policy Analysis Archives, 2000)
The widening gap between the increased use of technology in schools and the absence of computers in state-level testing programs raises important implications for policies related to the use of both technology and testing in schools. In this article, we summarize recent developments in the use of technology in schools and in state level testing programs. We then describe two studies indicating that written tests administered on paper underestimate the achievement of students accustomed to working on computers. We conclude by discussing four approaches to bridging the gap between technology and testing in U.S. schools.